Improvement of Prospective Teachers’ Reflective Skills Through Reflective Practices: A Time Series Quasi-Experimental Study (Journal of Asian Development Studies, 2024)
This study examined the effect of teachers' reflective practices on developing the reflective skills of prospective teachers. The research investigated the teachers' approaches in applying such practices in teaching to establish whether these reflective practices are essential and to what extent they benefit the prospective teachers. This research focused on a BS-level program in a private university. The study's research design was a Quasi-experimental design that employed a time series design with an intact group (section) of prospective teachers. The intact group was formed in the study sample. The research paradigm was positivist, followed by the time series design. The data was collected through face-to-face interaction using an observation scale. The researcher added questions about reflective practices measured against a 5-point scale. The researchers used reflective practices, such as a reflective classroom environment, self-evaluation, group discussion, and positive feedback. The teacher taught the English Language-IV (Prose and Translation) Program. There were two observations in a month and eight in four months and 16 weeks. The data was analyzed using visual analysis and one-way repeated measures ANOVA. Partial eta value (.953) revealed that reflective practices significantly affect prospective teachers' reflective skills. To improve prospective teachers' reflective skills, the researchers recommended using reflective practices to teach prospective teachers for their better performance.